2014
DOI: 10.1002/dmrr.2508
|View full text |Cite
|
Sign up to set email alerts
|

Association between bone mineral density and type 1 diabetes mellitus: a meta‐analysis of cross‐sectional studies

Abstract: A few studies have investigated the relationship between type 1 diabetes mellitus (T1DM) and bone mineral density (BMD) values. This meta-analysis was performed to explore differences between T1DM and healthy individuals in BMD values measured at five bone sites.We searched the database of PubMed for cross-sectional studies about the association of T1DM and BMD, and a meta-analysis was conducted.The results suggested significant association between T1DM and decreased BMD values of total body. The pooled mean d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 44 publications
2
44
0
2
Order By: Relevance
“…In agreement with our results, Gunczler et al, (1998) suggested that T1DM in children was associated with low bone turnover resulting in a decline in bone mass, which might manifest as osteopenia in the growing bone (Gunczler et al, 1998). Pan et al (2014), in a metaanalysis of cross-sectional studies, reports that T1DM is associated with a significantly lower BMD overall, and BMD (including total body, spine and femur) differences were also observed in patients <20 years old. However, bone loss among patients with T1DM <20 years old suggested that BMD may decrease relatively early in the course of the disease (Pan et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In agreement with our results, Gunczler et al, (1998) suggested that T1DM in children was associated with low bone turnover resulting in a decline in bone mass, which might manifest as osteopenia in the growing bone (Gunczler et al, 1998). Pan et al (2014), in a metaanalysis of cross-sectional studies, reports that T1DM is associated with a significantly lower BMD overall, and BMD (including total body, spine and femur) differences were also observed in patients <20 years old. However, bone loss among patients with T1DM <20 years old suggested that BMD may decrease relatively early in the course of the disease (Pan et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…Pan et al (2014), in a metaanalysis of cross-sectional studies, reports that T1DM is associated with a significantly lower BMD overall, and BMD (including total body, spine and femur) differences were also observed in patients <20 years old. However, bone loss among patients with T1DM <20 years old suggested that BMD may decrease relatively early in the course of the disease (Pan et al, 2014). Notably, osteopenia has been reported at the onset of T1DM, suggesting the existence of pathogenic mechanisms that operate before the overt manifestation of T1DM.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Considering importance of osteoporosis in the individual's activity and increased risk of pathological fractures in the future, determining prevalence and risk factors of the problem in children with type 1 DM and necessary treatments for its reduction is essential (13). Previous studies showed that type 1 DM causes reduction of bone density and ossification markers and increasing bone loss markers, and BMD is a good indicator for detecting changes in bone quality (14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%